2014
DOI: 10.1177/0969733014557115
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and perceived results of moral case deliberation

Abstract: The relevance of moral case deliberation for care practice received wide acknowledgement from the respondents. It can contribute to the team's cohesion as mutual understanding for one another's views is fostered. If implemented well, moral case deliberation has the potential to improve care, according to the respondents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 18 publications
4
67
0
Order By: Relevance
“…In the context of ethics applied in the clinical context, the top‐down approach has been defined as the application of knowledge in a process of deduction in light of relevant empirical facts, and in an impartial and value‐free manner . But ethical deliberation should occur both top‐down (here, according to the legal criteria that apply in the institution where the decision‐making takes place) as well as bottom‐up, in connection to the care practice . The care practices in which decision‐making about CCC is embedded emerge from the relationship between the care receiver and caregiver.…”
Section: A Care‐ethical Analysismentioning
confidence: 99%
“…In the context of ethics applied in the clinical context, the top‐down approach has been defined as the application of knowledge in a process of deduction in light of relevant empirical facts, and in an impartial and value‐free manner . But ethical deliberation should occur both top‐down (here, according to the legal criteria that apply in the institution where the decision‐making takes place) as well as bottom‐up, in connection to the care practice . The care practices in which decision‐making about CCC is embedded emerge from the relationship between the care receiver and caregiver.…”
Section: A Care‐ethical Analysismentioning
confidence: 99%
“…2 Further issues were to strengthen moral competencies and to develop routine in case of difficult questions. [3][4][5][6] Ethics consultations are also referred to as moral distress consultations 7 or moral case deliberations, 4 whereby the latter is described as being a part of ethics consultations. To ensure the quality of ethics consultations, evaluations of CECs were first discussed in 1996 8,9 and are now requested as standard in Germany by the Academy for Ethics in Medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The services often experience challenging situations where different values and arguments are emphasized. Some studies have demonstrated that ethics reflection has a positive role in supporting the staff in difficult decision-making processes (8)(9)(10)(11).…”
Section: Professionals' Perceptions Introductionmentioning
confidence: 99%
“…In this study we use the term ERG because in our view, the ERG can also involve the discussion of other topics, such as clinical-ethical values or other general topics. Other authors use terms like ethics case reflection (ECR) (12) or Moral case deliberation (MCD) (10,11,13). A study of doctors who had brought a case to a hospital Clinical ethics committees, showed that clinicians found it useful to discuss ethical problems, and that they appreciated the depth of the discussion (14).…”
Section: Professionals' Perceptions Introductionmentioning
confidence: 99%